The serum proteomic profile in patients with migraine - Yating Han; Yuan Wang; Xiajuan Zou; Huailian Guo; Huailian Guo (Frontiers in Molecular Neuroscience)
BackgroundMigraine is a paroxysmal headache disorder, which seriously affects the patients’ quality of life. However, the pathogenesis of migraine is not clear yet. Proteomics is an emerging technology for studying small molecules and protein components in biological systems. This study aimed to analyze the serum proteome of migraine patients and healthy controls and identify differentially expressed proteins, which could provide a reference for the study of biomarkers and pathophysiological mechanisms of migraine.MethodsFasting venous blood was collected, and serum was separated. Liquid chromatography–mass spectrometry was used to detect the proteome of the two groups, and MaxQuant was used to analyze the protein profile and identify the differentially expressed proteins.ResultsTwenty-seven migraine patients and 20 healthy people matching the age and sex ratio of the migraine group were collected. A total of 27 differentially expressed proteins were identified between migraine and control groups, which were mainly related to immune response, inflammation, glycolysis, lipid metabolism, neurotrophy and development, and so on. Subgroup analysis also identified several differentially expressed proteins between the migraine with aura and the migraine without aura groups and between the ictal and interictal migraine groups. Moreover, the signal pathways that may be related to migraine include the glycolysis/gluconeogenesis pathway and the hypoxia-inducible factor-1 signal pathway. Differentially expressed proteins are mainly distributed in the extracellular area. Related biological processes include complement activation, immunoglobulin receptor binding, and phagocytosis.DiscussionThe research screened out several differentially expressed proteins of migraine patients, which may be potential biomarkers, but it still needs verification in further studies with larger sample sizes. Various proteins related to inflammation, immune response, and energy metabolism are differentially expressed between the migraine group and the control group, suggesting that the pathogenesis of migraine may be related to inflammation, immunity, and energy metabolism disorders. In the future, we can further explore the therapeutic targets of migraine in terms of these biological processes.